2010
DOI: 10.1016/s0828-282x(10)70357-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of admission serum glucose level on in-hospital outcomes following coronary artery bypass grafting surgery

Abstract: I t has been confirmed that serum glucose (SG) levels are independently associated with both short-and long-term outcomes of patients with cardiovascular disease (1). In the setting of an acute myocardial infarction, hyperglycemia enhances the risk of morbidity and mortality independent of the patients' diabetes status (2). Hyperglycemia is also highly predictive of the occurrence of left ventricular failure and cardiac death in patients with acute coronary syndrome (3,4), and is associated with larger infarct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 14 publications
3
14
0
Order By: Relevance
“…25,31 Hyperglycemia has been associated with a high incidence of postoperative infections in both the pediatric and adult cardiac surgery population. 32,33 Increasing blood glucose concentrations have been shown to dampen innate immunologic processes. 34 In contrast to findings in our unpublished adult study, elevated blood glucose levels were not identified as potential risk factors for developing BSI in this cohort of children on HPN.…”
Section: Discussionmentioning
confidence: 99%
“…25,31 Hyperglycemia has been associated with a high incidence of postoperative infections in both the pediatric and adult cardiac surgery population. 32,33 Increasing blood glucose concentrations have been shown to dampen innate immunologic processes. 34 In contrast to findings in our unpublished adult study, elevated blood glucose levels were not identified as potential risk factors for developing BSI in this cohort of children on HPN.…”
Section: Discussionmentioning
confidence: 99%
“…1 Although the mechanisms remain unclear, glucose concentrations show a continuous relation with future cardiovascular disease in patients with or without diabetes and in the general population, beginning at concentrations well below those used to define diabetes. 1 These associations have been observed in ambulatory settings 1 and special ised hospital settings; [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] however, the relation between preoperative glucose concentration and morbidity in patients undergoing a broad range of noncardiac surgeries has not been systematically studied in large numbers of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Admission blood glucose levels were associated with significant morbidity after CABG surgery. 22 Our analyses indicated that there is a gradual increase in risk relative to blood glucose levels, regardless of the administration of insulin.…”
Section: Discussionmentioning
confidence: 69%